2011
DOI: 10.1152/jn.00279.2011
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism for antiepileptic drug action: vesicular entry may mediate the effects of levetiracetam

Abstract: A new mechanism for antiepileptic drug action: vesicular entry may mediate the effects of levetiracetam. J Neurophysiol 106: 1227-1239, 2011. First published June 8, 2011 doi:10.1152/jn.00279.2011 is one of the most commonly prescribed antiepileptic drugs, but its mechanism of action is uncertain. Based on prior information that LEV binds to the vesicular protein synaptic vesicle protein 2A and reduces presynaptic neurotransmitter release, we wanted to more rigorously characterize its effect on transmitter re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 41 publications
12
115
0
2
Order By: Relevance
“…It was also shown that the antiepileptic efficacy of levetiracetam and its derivatives correlated with their binding affinity to SV2A (7). Levetiracetam reduces presynaptic glutamate release particularly in neurons with a sustained and high frequency firing (8,9). A neuroprotective role of SV2A modulation was also suggested by a recent study demonstrating that levetiracetam suppresses neuronal network dysfunction and reverses synaptic and cognitive deficits in a mouse model of Alzheimer disease (27).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It was also shown that the antiepileptic efficacy of levetiracetam and its derivatives correlated with their binding affinity to SV2A (7). Levetiracetam reduces presynaptic glutamate release particularly in neurons with a sustained and high frequency firing (8,9). A neuroprotective role of SV2A modulation was also suggested by a recent study demonstrating that levetiracetam suppresses neuronal network dysfunction and reverses synaptic and cognitive deficits in a mouse model of Alzheimer disease (27).…”
Section: Discussionmentioning
confidence: 89%
“…Expressing Human SV2A-The antiepileptic drug levetiracetam specifically binds to SV2A and modulates its function (7)(8)(9). We found that the growth of hSV2A-expressing, hexose transport-deficient yeast cells on 2% galactose-containing medium was concentration-dependently inhibited by levetiracetam (Fig.…”
Section: The Antiepileptic Drug Levetiracetam Inhibits the Galactosedmentioning
confidence: 81%
See 1 more Smart Citation
“…The mechanisms are paradoxical ; the amplitudes of the late postsynaptic field potentials are decreased for hyperactive synapses, with minimal effect on normal synaptic transmission (7). Recent studies also showed that levetiracetam has antioxidant property (8,9), and inhibits NO level (10).…”
Section: Introductionmentioning
confidence: 99%
“…10 Its mechanism of action is distinct from that of the other antiepileptic drugs, [11][12][13][14] being presumed that it acts by modulating the function of the synaptic vesicle glycoprotein SV2A. [14][15][16][17][18][19][20][21][22] Its interesting pharmacokinetic properties together with its distinct chemical structure and mechanism of action make LEV unique among the marketed antiepileptic drugs. 9,11,23,24 For a better understanding of the pharmacodynamics of LEV, the characterization of its structure in solid and liquid state is crucial.…”
Section: Introductionmentioning
confidence: 99%